Integrating electrodermal biofeedback into pharmacologic treatment of grand mal seizures - Scrimali, Tullio; Tomasello, Damiana; Sciuto, Massimo (Frontiers in Human Neuroscience, 2015)
Electrodermal activity and electrodermal biofeedback, when integrated into pharmacologic treatments, are promising methods for grand mal seizures. They can be used to monitor the patient arousal and help the patient learn some new strategies for better coping with stress and anxiety. Our proposed method can possibly reduce the number of crises for patients who are dependent on pharmacologic therapy and can also improve their quality of life. This article describes the scientific background of electrodermal monitoring and electrodermal biofeedback for patients affected by grand mal seizures. In this study, we have reported a clinical case study. A patient is treated for two years with electrodermal biofeedback to augment pharmacologic treatments. The trial has been designed according to a “n=1 case study research”. Our results showed that our methods can achieve a significant reduction in grand mal seizures and sympathetic arousal. The patient in consideration was also relaxed and exhibited a greater competency in coping with stress. In addition, the patient’s sense of mastery and self-efficacy was enhanced.